Penerapan Pijat Tui Na Untuk Meningkatkan Berat Badan Pada Balita Dengan Gizi Kurang Di Puskesmas Juata - Sri Nurtilawati; Donny Tri Wahyudi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The growth and development in toddlers is influenced by the cheir nutritional status, which is related to feeding practices. Improper nutrition can hinder growth and development leading to decreased immunity. Tui Na massage is a non-pharmacological therapy that can address eating difficulties and increase appetite thereby aiding weight gain in toddlers. The objective of this study is to understand and apply nursing care to malnourished toddlers using Tui Na Massage innovation as a safe and effective non-pharmacological therapy to increasing weight. Nursing care for malnourished toddlers from families Tn. A and Tn.S included assessment, data analysis, nursing diagnosis, nursing plan, nursing implementation and evaluation from April 22-28 2024. Tui Na massage for six consecutive days was proved to increase appetite and added 0 .5 kg toddlers weight. Tui Na massage can be recommended as a safe, effective, cost-effective non pharmacological therapy that parents can regularly,and correctly administer to help increase the child's weight.